Merchants of Virtue: Hindus, Muslims, and Untouchables in Eighteenth-Century South Asia - Cherian, Divya (South Asia across the disciplines, 2023)
Merchants of Virtue explores the question of what it meant to be Hindu in precolonial South Asia. Divya Cherian presents a fine-grained study of everyday life and local politics in the kingdom of Marwar in eighteenth-century western India to uncover how merchants enforced their caste ideals of vegetarianism and bodily austerity as universal markers of Hindu identity. Using legal strategies and alliances with elites, these merchants successfully remade the category of "Hindu," setting it in contrast to "Untouchable" in a process that reconfigured Hinduism in caste terms. In a history pertinent to understanding India today, Cherian establishes the centrality of caste to the early-modern Hindu self and to its imagination of inadmissible others. "A refreshingly different perspective on the history of caste and untouchability in India, enlarging the field of scholarship from its focus on the colonial era by telling us how precolonial configurations of power in the locality shaped the everyday experience of caste." - GOPAL GURU, coauthor of The Cracked Mirror and Experience, Caste, and the Everyday Social "This provocative and empirically rich study offers a plenitude of fascinating insights into aspects of western Indian history ca. 1800, from kingship and caste hierarchy to abortion and alcohol consumption. Particularly innovative is its focus on the critical role played by merchants in articulating social identities that became widespread in modern times." - CYNTHIA TALBOT, author of The Last Hindu Emperor "A pathbreaking book that explodes essentialist views of the construction of Hindu and Muslim identities in precolonial India. Divya Cherian provocatively argues that the category of 'Hindu' was the primary locus for a system of radical othering that excluded Untouchables (and Muslims as Untouchables) through mechanisms of state, law, and everyday life." - CHRISTIAN LEE NOVETZKE, Professor of South Asian and Religious Studies, University of Washington